2018
DOI: 10.1155/2018/4187347
|View full text |Cite
|
Sign up to set email alerts
|

Combination Treatment of C16 Peptide and Angiopoietin-1 Alleviates Neuromyelitis Optica in an Experimental Model

Abstract: Neuromyelitis optica (NMO) is an autoimmune inflammatory demyelinating disease that mainly affects the spinal cord and optic nerve, causing blindness and paralysis in some individuals. Moreover, NMO may cause secondary complement-dependent cytotoxicity (CDC), leading to oligodendrocyte and neuronal damage. In this study, a rodent NMO model, showing typical NMO pathogenesis, was induced with NMO-IgG from patient serum and human complement. We then tested whether the combination of C16, an αvβ3 integrin-binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…We demonstrated that these pathological changes can be ameliorated by treatment with C16 peptide which delayed disease progression and severity. These findings are consistent with the results of our previous study using the EAE model (Zhang et al, 2018). The Tie2 KI and PI3K/Akt inhibitor LY294002 compromised the effects of C16, indicating the importance of the Tie2 and PI3K/Akt pathways in C16-mediated NMO therapy.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…We demonstrated that these pathological changes can be ameliorated by treatment with C16 peptide which delayed disease progression and severity. These findings are consistent with the results of our previous study using the EAE model (Zhang et al, 2018). The Tie2 KI and PI3K/Akt inhibitor LY294002 compromised the effects of C16, indicating the importance of the Tie2 and PI3K/Akt pathways in C16-mediated NMO therapy.…”
Section: Discussionsupporting
confidence: 94%
“…The presence of NMO-IgG distinguishes the NMO model from MS. NMO-IgG selectively binds to AQP4. Pathological characteristics of NMO include loss of AQP4 and GFAP, granulocyte and macrophage infiltration, as well as demyelination and axonal injury primarily in the spinal cord and optic nerves (Zhang et al, 2018). The pathogenicity of NMO-IgG (anti-AQP4 autoantibodies) and human complement has been found to contribute to the initial NMO model (Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations